2017
DOI: 10.1002/pssa.201700018
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of PTB7‐Th:C bulk heterojunction photocells under low‐light illumination: Critical effect of dark parallel resistance

Abstract: Solution-processed organic photocell is one of the most promising candidates for the permanent power source for wireless devices. Since the device is not necessarily to be placed outdoor, and indoor light is generally weaker than outdoor light by 2-3 orders of magnitude, the characterization of the photocell under low-light illumination is important for this purpose. In this study, bulk heterojunction photocells based on a lowenergy gap polymer poly [[4,8-bis[5-(2-ethylhexyl) [3,4-b]thiophenediyl]] (PTB7-Th) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…However, the loss becomes high enough to skew the current-voltage curve to lower the FF of the device at a high illumination level and eventually limits the short-circuit photocurrent. The increased FF at low illumination intensity is also observed in photovoltaic devices based on organic semiconductors [15][16][17][18][19] and is considered as a key for the increased PCE at a low illumination level of the class of photovoltaic cells. The PCEs at 10L 0 and 20L 0 are found to be approximately 39% and 23% of the PCE at L 0 , respectively.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…However, the loss becomes high enough to skew the current-voltage curve to lower the FF of the device at a high illumination level and eventually limits the short-circuit photocurrent. The increased FF at low illumination intensity is also observed in photovoltaic devices based on organic semiconductors [15][16][17][18][19] and is considered as a key for the increased PCE at a low illumination level of the class of photovoltaic cells. The PCEs at 10L 0 and 20L 0 are found to be approximately 39% and 23% of the PCE at L 0 , respectively.…”
mentioning
confidence: 95%
“…Therefore, photovoltaic devices based on other materials with wider bandgap energy than c-Si such as amorphous silicon (a-Si), III-V semiconductors, organic semiconductors, dye-sensitized TiO 2 , and lead-halide perovskite are attracting much attention of the researchers for indoor light harvesting. [11][12][13][14][15][16][17][18][19][20][21][22][23][24] A semiconductor with wider bandgap energy has smaller intrinsic carrier concentration and thus is expected to yield smaller dark saturation current density, which is another key for efficient indoor photovoltaic cells because the photocurrent density under indoor illumination condition approaches the dark saturation current density.…”
mentioning
confidence: 99%
“…Although the full description of solar cell characteristics requires the numerical solution of a set of differential equations, such model is so complicated to be implemented into the electronic circuit design software. Suitable equivalent‐circuit model of a solar cell is not only necessary for designing efficient electronic circuit powered by the solar cell, but also useful for understanding the loss mechanism taking place in the solar cell …”
Section: Introductionmentioning
confidence: 99%
“…Such discrimination requires a systematic study including the collection of suitable set of data such as the dependence of estimated circuit parameters on experimental condition like temperature or illumination light intensity. For example, it has been reported that R p in organic solar cell is inversely proportional to the illumination light intensity while that in Si solar cell slightly depends on the light intensity, reflecting the difference in the carrier mobilities in the active material. It is unquestionable that accurate estimation of circuit parameters is critically important for such purpose.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation